Efficient Compiler Design for a Geometric Shape Domain-Specific Language: Emphasizing Abstraction and Optimization Techniques - Gupta, Priya; ManiKiran, Terala; Purushotham, Mailapalli; Suriya, L Jeya; Naga Venkata, Rasamsetty; Nanda, Sambhudutta (EAI Endorsed Transactions on Scalable Information Systems, 2023)
The research paper represents a novel approach to the design and optimization of a compiler for a domain-specific language (DSL) focused on geometric shape creation and manipulation. The primary objective is to develop a compiler capable of generating efficient machine code while offering users a high level of abstraction. The paper begins with an overview of DSLs and compilers, emphasizing their importance in software development. Next, it outlines the specific requirements of the geometric shape DSL and proposes a compiler design that addresses them. This innovative approach considers DSL’s unique features, such as shape creation and manipulation, and aims to generate high-quality machine code. The paper also discusses optimization techniques to enhance the generated code’s quality and performance, including loop unrolling and instruction scheduling. These optimizations are particularly suited to the DSL, which focuses on geometric shape creation and manipulation and are integral to achieving efficient machine code generation. In conclusion, the paper emphasizes the novelty of this approach to DSL compiler design and anticipates exciting results from testing the compiler developed for the geometric shape DSL.